Kebutuhan Keluarga Pasien Critical Care Unit (CCU) - repindra oktari; Hellena Deli; Lita Lita (LPPM Universitas Abdurrab, 2021)
Family Needs of Patients Admitted to Critical Care Unit (CCU) Abstract The growing threat of patients’ death will impact on their family’s worry and stress which will negatively affect the role of the family as a part of the support system for the patient. The purpose of this study is to determine family needs of patients admitted to CCU of Arifin Achmad General Hospital of Riau Province. This is a quantitative study using descriptive design with 21 respondents chosen using consecutive sampling technique. The data were collected using questionnaire and then analyzed using univariate analysis. The study found that, regarding the need for service guarantees, 85.7% respondents stated that it was very important to understand the purpose of the medication and health treatment given to the patient; regarding the need for information, 66.7% respondents stated that it was very important to know the real condition of the patient; regarding the need for mental support from the family, 71.4% respondents stated that it was very important to have support from the family; regarding the need for convenience, 42.9% respondents stated that it was important and very important that they were provided with washroom close to the waiting room as well as the waiting room close to the intensive room; and regarding the need for closeness, 38.1% respondents stated that it was very important to be able to visit the patient at CCU with one member of the family. It can be concluded that the need for understanding the purpose of the medication and health treatment given to the patient is the one that patients’ family need the most. It is suggested that the nurses prioritize providing nursing care for the most needed family needs. Key words: CCU, Family needs. Kebutuhan Keluarga Pasien Critical Care Unit (CCU) Abstrak Besarnya ancaman kematian pasien akan memiliki dampak kecemasan dan stres keluarga dan berdampak pada peran keluarga sebagai support system menjadi tidak maksimal. Penelitian ini bertujuan untuk menggambarkan kebutuhan keluarga pasien CCU di RSUD Arifin Achmad Provinsi Riau. Jenis penelitian ini adalah kuantitatif dengan desain deskriptif, pengambilan sampel menggunakan teknik consecutive sampling, jumlah sampel dalam penelitian ini sebanyak 21 responden. Alat pengumpulan data menggunakan kuesioner dan analisis data dilakukan secara univariat. Hasil penelitian didapatkan pada kebutuhan jaminan pelayanan 85.7% responden menyatakan sangat penting untuk mengetahui tujuan pengobatan dan tindakan perawatan yang diberikan, pada kebutuhan informasi 66.7% responden menyatakan sangat penting mengetahui kondisi pasien yang sebenarnya, pada kebutuhan dukungan mental keluarga 71.4% responden menyatakan sangat penting mendapatkan dukungan antar keluarga, pada kebutuhan kenyamanan 42.9% responden menyatakan penting dan sangat penting untuk tersedia kamar mandi dekat ruang tunggu dan tersedia ruang tunggu didekat ruang intensif, serta pada kebutuhan kedekatan 38.1% responden menyatakan sangat penting untuk mengunjungi pasien diruang intensif (CCU) bersama salah satu kerabat. Dapat disimpulkan bahwa kebutuhan mengetahui tujuan pengobatan dan tindakan perawatan yang diberikan merupakan kebutuhan yang paling dibutuhkan keluarga. Kepada perawat disarankan untuk memprioritaskan asuhan keperawatan terhadap kebutuhan keluarga yang paling dibutuhkan. Kata kunci : CCU , Kebutuhan keluarga.